Study of the effect of steel plate thickness and opening characteristics on the seismic behavior of composite steel shear wall with reinforced concrete cover - Al-Khafaji, Hayder M. J. (Edelweiss Applied Science and Technology, 2025)
This study explores the impact of steel plate thickness, concrete cover, and the presence of openings on the seismic performance of composite shear walls. A total of 19 numerical models were analyzed using nonlinear static (pushover) analysis, with parameters including plate thickness, reinforced concrete cover, and different opening types. Results indicate that increasing the steel plate thickness significantly enhances the ultimate load, stiffness, and energy dissipation capacity. For example, models with concrete cover exhibited improved performance, with ultimate load ratios of up to 12.98 times the control model. In contrast, models with openings, particularly door openings, showed a decline in performance, with load ratios of up to 5.75 times the control model. Stiffness was also reduced in models with openings, with door-opening models showing the lowest stiffness. Energy dissipation improved with increased plate thickness and concrete cover, with the T16Co model dissipating 7.7 times more energy than the control model. The findings highlight the importance of steel plates and concrete encasement in improving seismic resistance, while the presence of openings reduces the wall’s ability to resist lateral loads and absorb energy.